Forward-scattering radar (FSR) ground target signal processing for human motion / Muhammad Najmi Afiq Yahya - Yahya, Muhammad Najmi Afiq (2016)
The importance of human surveillance and detection for military activities such as border protection or commercial activities such as human trespassing need to be considered in detail. An efficient monitoring system in the area that is difficult to be accessed is required for safety of the people which can be done with the implementation of advanced technology such as radar sensor. This paper focused on the comprehensive analysis studies of human's motion by using forward-scattering radar (FSR) which may differ according to their miscellaneous types of activity such as walking and running. Three human targets with different types of movement and one vehicle were tested when they crossed the FSR baseline and two different operating frequencies of 2.5GHz and 3 GHz were used during the experimental procedure. A simulation with several stages of signal processing were conducted by using MATLAB in order to extract the information of the target and to analyze the character of the information obtained.